The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4172/2155-9597.1000129
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Taeniasis in the Bunkpurugu-Yunyoo District of Northern Ghana

Abstract: Although Taenia solium infestation and cysticercosis have been documented as the main causes of acquired epilepsy and their recognition as important public health hazards has risen over the past 10 years, there is lack of information on the disease burden due to Tape worm infestation and its associated risk factors in the rural communities of northern Ghana. This study was conducted to evaluate the prevalence of Taeniasis and document its associated risk factors. The study describes the results of a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 15 publications
2
18
1
Order By: Relevance
“…A recent review of previously published studies across Africa demonstrated taeniasis prevalence ranging from 0% to 8.7% (although these studies do not use a standardised diagnostic protocol) [ 1 ]. A higher prevalence of 13.15% has been reported from Ghana, based on detection by microscopy [ 26 ]. The detected prevalence of taeniasis based on direct observation of Taenia spp.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of previously published studies across Africa demonstrated taeniasis prevalence ranging from 0% to 8.7% (although these studies do not use a standardised diagnostic protocol) [ 1 ]. A higher prevalence of 13.15% has been reported from Ghana, based on detection by microscopy [ 26 ]. The detected prevalence of taeniasis based on direct observation of Taenia spp.…”
Section: Discussionmentioning
confidence: 99%
“…A higher prevalence of 13.15 and 9.6% Taenia spp. were reported in studies conducted in Ghana [26] and Nigeria [27] respectively. However, this study reported a low prevalence of 2.9% Taenia spp., which is similar to reports previously published across Africa demonstrating taeniasis prevalence ranging from 0 to 8.7%, although these studies do not use a standardized diagnostic protocol [28].…”
Section: Discussionmentioning
confidence: 73%
“…There are indications that pork consumption is increasing in sub-Saharan Africa, while preparation methods in the region often do not effectively kill the cysticerci (Assana et al, 2013). Heat resulting from boiling and frying the pork passes through the meat to a greater extent and is more likely to kill the cysts, compared to heat from roasting or barbecue grilling, as reported in Nigeria (Edia-Asuke, et al, 2015).Studies conducted in Ghana, Nigeria and Burkina Faso indicated that those who ate pork with cysticerci and those who ate lightly cooked pork soups in the markets had higher probabilities of taeniasis (Bimi et al, 2012;Weka et al, 2013;Carabin et al, 2015). In Benin it is frequently eaten in form of a meat product named "kpete"…”
Section: Pork Preparation and Consumptionmentioning
confidence: 99%